Climate Change and Milk Price Volatility in Indonesia - Arief Daryanto; Diani Aliya Sofia; Sahara Sahara; Antonya Rumondang Sinaga (International Journal of Economics and Financial Issues, 2020)
The international food crisis from 2007 to 2010 impacts the fluctuation of world's food prices. Indonesia is one of the developing countries that are vulnerable to volatility in food prices because food is a necessity that is still partly imported and hence impactingdomestic prices.  This problem has been excerbated by tthe fact that domestic fresh milk production made a relatively small contribution to the availability of milk to meet Indonesia's consumption. This study aims to analyze the volatility of fresh milk prices in three largest milk producer regions in Indonesia, namely East Java, West Java, and Central Java, from June 2015 to December 2018. The study used ARCH GARCH model. The results of this study shown that fresh milk prices in West Java was volatile and it was influenced by the volatility of the previous period. Climate change and feed prices yielded positive responses on the volatility of fresh milk price in West Java.  Subsequently, it achieved a stable price level in the long run. In the short run, the highest response of the milk price volatility shock was shown by the West Java's fresh milk price volatility itself.